A critical review on training evaluation models : A search for future agenda - Badriya, Ambu-Saidi; Fung, C. Y.; Kristina, Turner; Agnes Lim, Siang Siew (UNIMAS Publisher, 2024)
This paper delves into the intricate landscape of training transfer evaluation, exploring some models, strengths, and areas for improvement in assessing the effectiveness of training programs. This paper aims to analyse and compare training transfer evaluation models using a scoping review methodology. By examining their strengths, weaknesses and unique characteristics, the paper seeks to pinpoint opportunities for enhancement. The discussion centres around seminal works such as Kirkpatrick's Four-Level Model, Kaufman and Keller's Five Levels of Evaluation, the Phillips Return on Investment Model, Warr et al.’s Context, Input, Reaction and Outcome Model and Brinkerhoff’s Six Stage Model, Bushnell’s input, process, output model. The paper underscores the importance of a comprehensive and adaptable approach to training transfer evaluation, emphasising the need for hybrid models that integrate strengths while addressing weaknesses. The exploration extends to measuring tools and research methods that enhance evaluation practices. The sequential explanatory mixed methods design emerges as an exemplar of a research methodology that seamlessly combines quantitative and qualitative approaches to offer a richer understanding of training transfer. As the paper concludes, it advocates for continuous research efforts to refine models, incorporate emerging technologies, and align evaluation practices with learning and organisational development dynamics. By revealing gaps in current knowledge and identifying previously unknown areas for improvement in training transfer, this paper contributes novel insights to the field of training transfer.